Secreted factors from adipose tissue increase adipogenic differentiation of mesenchymal stem cells - Wu, L. (Cell Prolif, 2012)
OBJECTIVES: Adipose tissue engineering is one of the hottest topics in the field of regenerative medicine. Fat tissue has been considered as an abundant and accessible source of adult stem cells by tissue engineers, since it gives rise to adipose stem cells. However, recent reports have pointed out that adipose tissue, as a secretory and endocrine organ, might secrete cytokines that regulate body functions such as metabolism, infammation and more. In this study, we aim to investigate the adipogenic‐inducing factors secreted by fat tissue. MATERIALS AND METHODS: Conditioned medium were collected by culturing fat tissue fragments in plastic flasks. Mesenchymal stem cells (MSCs) cultured in conditioned medium (CM) to test the adipogenic‐inducing factors. Oil red O staining, reverse transcription/polymerase chain reaction and immunocytofluorescent staining were performed to examine the differentiation of MSCs in CM. RESULTS: MSCs cultured in CM of adipose tissue spontaneously differentiated into adipocytes. Furthermore, supplementation of insulin or dexamethasone to CM accelerated the process of lipid accumulation of differentiated MSCs. DISCUSSION: Results from this study demonstrated that fat tissues secrete small molecules, which induce adipogenic differentiation of MSCs. CONCLUSIONS: Our study provides clues for improving adipose tissue engineering by using fragmented adipose tissue as sources of fat‐inducing factors.